Exploring differences in oral presentation modes: Does video recording really improve students performances? - Refanja Rahmatillah; Ana Elvia Jakfar; Firman Parlindungan; Merina Devira (Studies in English Language and Education, 2025)
Video recording has been proven beneficial for learning, and it might help improve students presentation skills and confidence. To examine the assumption related to students presentation skills and confidence, this study explored the differences in English as a foreign language (EFL) students performances, preparations, and preferences between video recording and in-class presentation. Forty college students from various majors enrolling in an English course were randomly sampled to participate in this study. Twenty of them performed presentations through video recording, and the rest in class. The students were given an online questionnaire about their preparations and preferences between the two modes. Their performances and preparation time were compared, and their preferences were analyzed. The results show no significant difference in the overall performances between those two groups of students (M = .1565), t(38) = 1.114, p .272. However, there was a significant difference in the aspect of eye contact and gestures (M = .5250), t(38) = 2.161, p = .037, indicating that the students presented through video recordings were more confident and used more gestures. Moreover, it was found that practice time did not correlate with the students performances r(38) = .025, p = .914. In addition, the students were not consistent with their preferences; while the majority (68.9%) agreed that they were more confident presenting through video recordings, 61.2% expressed a preference for in-class presentations. Therefore, it is recommended that EFL teachers assign a presentation mode that best suits students context since each mode has its strengths and shortcomings.